Identifikasi Potensi Materi Ajar Invertebrata di Area Pantai Kecamatan Serasan Pada Materi Pelajaran IPA - Weldi, Weldi (BIO-EDU: Jurnal Pendidikan Biologi, 2020)
The beach in the Serasan sub-district is one of the beaches that has local potential that is underutilized. Therefore it is necessary to conduct research that is intended to provide information to teachers about the location that can be done outside the classroom learning process. This research uses descriptive qualitative and exploration methods. The technique of collecting data uses observation, collection, interviews, and documentation. The results of the study of the potential of invertebrate animals in the Coastal District of Serasan District consisted of invertebrate animals in the phylum Molluscs, Arthropods, Coelenterata, and Echinoderms. The local potential of Invertebrate animals in the Coastal District of Serasan District is in accordance with the learning objectives of Invertebrate (Animalia) material in class X, namely Determining the General Characteristics of Invertebrate Animals (body lining, body cavity, body symmetry, and replacement); Determine the life cycle of invertebrates; Determine the classification of invertebrates; determine the role of invertebrates (explain the role of animals for life). The local potential of Inveretebrata animals in the Pantai District of Serasan District as a place for the Biology High School learning process.